Advancements in Robotics and AI Transforming Surgery and Rehabilitation - Zebanaz Jahangir Ansari; Ashwini Aher; Sunil Namdeo Thitame (Journal of Pharmacy and Bioallied Sciences)
The use of AI and robotics in surgery and rehabilitation is transforming healthcare by improving accessibility, precision, and customization. Robotic devices provide for safer, more accurate, and shorter recovery periods during minimally invasive procedures. By offering real-time decision support and predictive analytics during procedures, AI enhances these developments. AI-powered solutions in rehabilitation use data from wearables and remote monitoring to generate customized treatment plans, increasing access to care, even in underprivileged areas. Through innovation, moral responsibility, and teamwork, robotics and AI are revolutionizing patient care and establishing new benchmarks for healthcare delivery. Robotic devices provide for safer, more accurate, and shorter recovery periods during minimally invasive procedures. By offering real-time decision support and predictive analytics during procedures, AI enhances these developments. AI-powered solutions in rehabilitation use data from wearables and remote monitoring to generate customized treatment plans, increasing access to care, even in underprivileged areas. Through innovation, moral responsibility, and teamwork, robotics, and AI are revolutionizing patient care and establishing new benchmarks for healthcare delivery.